2010
DOI: 10.1007/s11111-010-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Population and pavement: population growth and land development in Israel

Abstract: This research examines land use change in Israel--an intriguing but understudied setting with regard to population-environment dynamics. While Israel is fairly unique with regard to its combined high levels of economic prosperity and high population growth, this case study has relevance for developed countries and regions (like the south and southwest regions of the USA) which must balance population growth and urban development with open space conservation for ecosystem services and biological diversity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 68 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…Thus, it can be observed that the development of the housing market varies considerably in time and space. The spatial and temporal dynamics concern different levels of the spatial hierarchy, with economic and demographic processes relating to housing changes at these hierarchical levels in different ways [20,21]. For example, Reichert [13] claims that the prices at the national level are affected to the greatest extent by mortgage interest rates, while at the regional level-by population migration, employment rate and household income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it can be observed that the development of the housing market varies considerably in time and space. The spatial and temporal dynamics concern different levels of the spatial hierarchy, with economic and demographic processes relating to housing changes at these hierarchical levels in different ways [20,21]. For example, Reichert [13] claims that the prices at the national level are affected to the greatest extent by mortgage interest rates, while at the regional level-by population migration, employment rate and household income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is evidence that the quantity of urban open spaces is shrinking (Orenstein and Hamburg, 2010; Shoshany and Goldshleger, 2002). Nevertheless, some open spaces remain within cities (Tardin, 2012).…”
Section: Spatial Evolution Of Cities and Urban Open Spacesmentioning
confidence: 99%
“…Construction activity demonstrates high variability in time and space (ORENSTEIN, HAMBURG 2010;ANGEL et al 2011;INOSTROZA et al 2013). The results of research on the diversity of construction activity in a spatial perspective have been presented, among others, by BEENSTOCK and FELSENSTEIN (2015) with the use of non-stationary panel data, concerning selected areas of Israel.…”
Section: Previous Researchmentioning
confidence: 99%